Programa de controle de surto de escorpião Tityus serrulatus, Lutz e Mello 1922, no município de Aparecida, SP (Scorpiones, Buthidae). - Cruz, E. F.; Yassuda, C. R.; Jim, J.; Barraviera, Benedito [UNESP] (FapUNIFESP (SciELO), 1995)
A scorpion control program was proposed for the town of Aparecida (SP), an endemic region of Tityus serrulatus. Clusters of scorpions in urban and rural areas, environmental degradation of the town's outskirts and new scorpion procreation and dispersal habitats were studied. In addition, infrastructure problems such as the disposal and collection of residential and municipal refuse, sanitation (sewage and storm sewer), condition of vacant lots and constructions in the urban area were evaluated. After an epidemiological study, educational measures such as the distribution of pamphlets, cleaning group work, visits to residences and cooperation from High School teachers and students were also suggested. Chemical control was indicated in high-risk sites, especially those of near-school buildings. Furthermore, the use of natural predators was also mentioned within the present sanitation regulations for urban areas. The authors assert that these procedures must be integrated and continued uninterruptedly for several years. They also suggest a collaborative work with those responsible for the dengue eradication program, as well as the institution of the scorpion study week, which would greatly contribute to the education of the population, to preventive programs and to scorpion control.
A control program for an outbreak of the scorpion Tityus serrulatus, Lutz and Mello 1922 in the town of Aparecida, São Paulo state (Scorpiones, Buthidae)
Keywords: animal; Brazil; health education; human; methodology; pest control; rural population; scorpion; spider bite; urban population; Animal; Arachnidism; English Abstract; Health Education; Human; Pest Control; Rural Population; Scorpions; Urban Population